Future prospects of biomass waste as renewable source of energy in Pakistan: A mini review - Ahmad, Waqas; Nisar, Jan; Anwar, Farooq; Muhammad, Faisal (Elsevier, 2023)
Life requires energy, which is a fundamental need. The first fuel used by humans was wood, which they later replaced with fossil fuels. Scientists and decision-makers are working to switch to renewable energy sources since fossil fuels have numerous negative environmental effects. In this regard, biomass is one of the most significant sources of clean, ecologically friendly energy that comes from living things and has the potential to meet demand. In light of the current energy crisis, it is crucial to use local biomass resources to generate energy. In this paper, we provided a thorough overview of biomass, its components, and the utilization of biochemical and thermochemical methods for converting biomass into useful products while also taking into account Pakistan's perspective on renewable energy sources. Additionally, the use of biomass as a renewable energy source in Pakistan and its potential for the country's energy sector are thoroughly examined.